Contemporary Transformations of Indigenous Medicine and Ethnic Identity - De Burgos, Hugo (Anthropologica, 2014)
Over the past two decades, many Indigenous leaders in Nicaragua have been promoting the idea that, beyond its vital and obvious medical value, Indigenous medicine represents an important political tool for claiming and signalling cultural boundaries. This article explores the particular conditions under which medical practices and ideas in a Nahua community become both objective and subjective markers of ethnic identity and cultural resistance. Within this context, I introduce the concept derivative functions of medicine to describe a role of medicine in non-medical matters, including the creation and maintenance of an ethnically distinct sense of group identity.